Genes 16S RNA ribossomal e pld como marcadores moleculares para identificação genotípica de amostras clínicas de Corynebacterium spp. (Caderno de Ciências Agrárias, 2016)
The genetic characterization of species is essential when you want to elect a vaccine strain or control the spread of outbreaks of a disease in a region. The 16S rRNA and pld Corynebacterium pseudotuberculosis genes play an important role as markers for bacterial genotype identification. The aim of this study was to validate an “in house” molecular methodology for genetic identification of Corynebacterium spp. isolated from clinical samples maintained in the laboratory. For this purpose, eleven isolates were reactivated in Brain Heart Infusion broth. The grown colonies identified as Gram-positive bacilli were submitted to chromosomal DNA extraction with KAPAExtract® kit according to manufacturer's recommendations. The extracted chromosomal DNA was quantified by 1.5% agarose gel electrophoresis and then subjected to duplex PCR with specific primers for the genus and species of Corynebacterium pseudotuberculosis. The amplicons generated were analyzed by 2.0% agarose gel electrophoresis. None of the isolated amplified the target genes for genus and specific species for those expected to be C. pseudotuberculosis. The positive control, C. pseudotuberculosis CIP102968 amplified fragments of 813 and 201 base pairs which corresponding to the 16S rRNA (genus specific) and pld genes (species specific) respectively. The negative control, Escherichia coli ATCC® 25922 do not amplified any target genes as expected. The results showed the need for improvement in the sampling techniques and previous microbiological identification preceding the molecular identification step and they are extremely important for precise genotype identification of strains of C. pseudotuberculosis.